Financial crises and Turkey case: (a discussion on Turkish twin financial crises in 200-2001 & data dissemination problem and early warning systems - Altuğ, Özgür (My University, 2002)
Bu çalışma finansal krizlerin mantığını anlamak ve kriz sonrası ortaya çıkan durumu ortaya koymak amacıyla ihtiyaç duyulan bilgileri içermektedir. Çalışma, finansal krizlerle ilgili aşağıdaki detayları kapsıyor: finansal kriz literatürü, bankacılık krizlerinin nedenleri, Türkiye örneği, Türkiye'deki veri yayınlama problemi, Türkiye'deki finansal krizlerin tahmin edilebilirliği ve erken uyarı sistemleri. Finansal krizlerle ilgili gerekli bilginin sunulmasından sonra tez, Türkiye örneğini açıklamaya çalışıyor. Krizlere Bağımlı denilebilecek bir ülke olan Türkiye, Kasım 2000 ve Şubat 2001 döneminde iki finansal kriz atlattı ve sabit kur sistemi bırakıldıktan hemen sonra IMF tarafından hazırlanan uygulamadaki stabilizasyon programından vazgeçti. Bazıları krizlerin ikiz krizler olduğunu ifade ederken, kimilerine göre krizler birbirinden bağımsız krizlerdi. Tezde bu tip krizlerle ilgili farklı görüşler yeralıyor. Ayrıca bu çalışma daha kapsamlı olarak, makroekonomik gelişmelerle bankacılık sektörü arasındaki yakın ilişkiyi değerlendiriyor. Bu ilişki kapsamında tezin sonunda Türkiye'deki finansal krizlerin tahmin edilmesine ilişkin bir erken uyarı sistemi uygulaması yeralır. This study provides necessary information in an attempt to understand the logic, consequences and aftermath of the financial crises. It exhibits the following accurate details of a financial crisis: financial crises literature, causes of banking crises, Turkey case, data dissemination problem in Turkey, predictability of financial crises in Turkey and early warning systems. Following the presentation of necessary information regarding the financial crises, the thesis attempts to explain the Turkey case. As a so called addicted to crises country, Turkey faced with two financial crises in November 2000 and February 2001 and the ongoing stabilisation program, supported with an IMF-backed program, had been eliminated, just after the fixed exchange rate regime has been abandoned. Some argued that the crises were twin crises and some argued that the crises were independent from each other. Different views regarding the reasons for such crises had been listed. This study concentrates mostly on the facts, which prove the close relation between the macroeconomic fundamentals and financial sector. In the context of this relation, an early warning system implementation for Turkey has been submitted in the last part of the thesis.
Keywords: Finansal Kriz